2001
DOI: 10.1074/jbc.m100787200
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Biophysical Evidence for γ2 Subunit Association with Neuronal Voltage-activated Ca2+Channels

Abstract: A novel gene (Cacng2; ␥ 2 ) encoding a protein similar to the voltage-activated Ca 2؉ channel ␥ 1 subunit was identified as the defective gene in the epileptic and ataxic mouse, stargazer. In this study, we analyzed the association of this novel neuronal ␥ 2 subunit with Ca 2؉ channels of rabbit brain, and the function of the ␥ 2 subunit in recombinant neuronal Ca 2؉ channels expressed in Xenopus oocytes. Our results showed that the ␥ 2 subunit and a closely related protein (called ␥ 3 ) co-sedimented and co-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
116
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(123 citation statements)
references
References 31 publications
4
116
3
Order By: Relevance
“…These and rolling Nagoya mice (with a further mutation on Cacna1a but not showing absence seizures) show ataxia and a wide variety of other central nervous system changes. The stargazer mouse has a mutation in Cacng2 that alters the function of Ca v 2.1 and Ca v 2.2 77 and modifies the cell surface expression of AMPA receptors. 78 The mutation in the lethargic mouse interferes with the ␤ 4 subunit modulatory action on the ␣ 1 subunit Ca v 2.1 and Ca v 2.2 although some compensatory subunit insertions ("reshuffling") may occur.…”
Section: Voltage-gated Calcium Channelsmentioning
confidence: 99%
“…These and rolling Nagoya mice (with a further mutation on Cacna1a but not showing absence seizures) show ataxia and a wide variety of other central nervous system changes. The stargazer mouse has a mutation in Cacng2 that alters the function of Ca v 2.1 and Ca v 2.2 77 and modifies the cell surface expression of AMPA receptors. 78 The mutation in the lethargic mouse interferes with the ␤ 4 subunit modulatory action on the ␣ 1 subunit Ca v 2.1 and Ca v 2.2 although some compensatory subunit insertions ("reshuffling") may occur.…”
Section: Voltage-gated Calcium Channelsmentioning
confidence: 99%
“…The ␥ 2 -protein is only 25% identical to skeletal muscle ␥ and may play different physiological roles. Immunoprecipitation studies have shown that ␥ 2 may be a subunit of both HVA Ca v 2.2 Ca 2ϩ channels and glutamate receptors of the AMPA class (74,190,366). Coexpression of ␥ 2 inhibits the expression of Ca v 2.1 and Ca v 2.2 channels in the presence of ␣ 2 ␦ 1 and has minor effects on their biophysical properties (190,346).…”
Section: E Auxiliary Subunits?mentioning
confidence: 99%
“…Immunoprecipitation studies have shown that ␥ 2 may be a subunit of both HVA Ca v 2.2 Ca 2ϩ channels and glutamate receptors of the AMPA class (74,190,366). Coexpression of ␥ 2 inhibits the expression of Ca v 2.1 and Ca v 2.2 channels in the presence of ␣ 2 ␦ 1 and has minor effects on their biophysical properties (190,346). In contrast, ␥ 2 had little effect on Ca v 3.3 expression, although it could slow the decay of the tail current (145).…”
Section: E Auxiliary Subunits?mentioning
confidence: 99%
“…It has been suggested that the change of [Ca 2ϩ ] i in local environment regulates the binding of chaperone proteins to AMPA receptors or phosphorylation of AMPA receptors (1). Based on recent studies (5,8,(22)(23)(24) and biochemical data in this study (Fig. 2), PSD95 or Ca 2ϩ channel ␥ 2 subunits (stargazin) could be a candidate chaperon protein modulating AMPA receptor trafficking depending on the Ca 2ϩ influx through Ca 2ϩ channels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the association of the ␥ subunits (␥ 2 and ␥ 3 ) with neuronal Ca 2ϩ channels has recently been established (5,6), which is similar to the association of ␥ 1 subunit with skeletal Ca 2ϩ channels (7). Interestingly, a role of the ␥ 2 subunits (stargazin) in the trafficking͞clustering of AMPA receptors has been reported (8)(9)(10)(11).…”
mentioning
confidence: 91%